Islamic Education Resilience: How Pesantren Maintain Authenticity in the Age of Artificial Intelligence (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2025)
The quick growth of artificial intelligence (AI) has revolutionized education systems throughout the world, posing fresh challenges for traditional Islamic educational institutions, notably pesantren in Indonesia. This research explores the resilience of Islamic education in pesantren and examines how these schools uphold the genuineness of religious knowledge, values, and learning traditions in the face of technological change. This study uses a qualitative library research technique and critical content analysis to determine that pesantren resilience is built upon three fundamental pillars: (1) cultural resilience through the preservation of classical Islamic scholarship (turāth), sanad-based knowledge transmission, and adab; (2) pedagogical resilience through embodied learning models such as halaqah, talaqqī, sorogan, and role-modeling (uswah); and (3) institutional resilience through selective and value-based adaptation of digital technologies without compromising core identity. Although AI improves administrative efficiency and accessibility, it cannot replicate the experiential knowledge, individual mentoring, or moral and spiritual authority that are at the heart of pesantren instruction. This research presents a techno-moderate pesantren model that combines technological advancement with the preservation of Islamic scholarly authenticity.